2014
DOI: 10.1099/ijs.0.058354-0
|View full text |Cite
|
Sign up to set email alerts
|

Acetobacter sicerae sp. nov., isolated from cider and kefir, and identification of species of the genus Acetobacter by dnaK, groEL and rpoB sequence analysis

Abstract: Acetobacter sicerae sp. nov., isolated from cider and kefir, and identification of species of the genus Acetobacter by dnaK, groEL and rpoB sequence analysis T and LMG 27543 was C 18 : 1 v7c. The major ubiquinone present was Q-9 and the DNA G+C contents of LMG 1531 T and LMG 27543 were 58.3 and 56.7 mol%, respectively. The strains were able to grow on D-fructose and D-sorbitol as a single carbon source. They were also able to grow on yeast extract with 30 % D-glucose and on standard medium with pH 3.6 or conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 43 publications
4
9
0
Order By: Relevance
“…Yet, the finding of A. tropicalis through metagenomic recruitment plotting was not in accordance with the culture-dependently isolated and identified A. senegalensis (both 16S rRNA and dnaK gene sequencing). However, both species differ only 4 and 10 nucleotides in their 16S rRNA and dnaK genes, respectively (this study; Li et al, 2014). Hence, the present study showed not only the complementarity of the combined use of culture-dependent and culture-independent methods regarding species detection and identification, which has been commonly employed since more than 20 years, but also the provision of both qualitative and quantitative data regarding species distribution.…”
Section: Sourdough Samplesupporting
confidence: 50%
“…Yet, the finding of A. tropicalis through metagenomic recruitment plotting was not in accordance with the culture-dependently isolated and identified A. senegalensis (both 16S rRNA and dnaK gene sequencing). However, both species differ only 4 and 10 nucleotides in their 16S rRNA and dnaK genes, respectively (this study; Li et al, 2014). Hence, the present study showed not only the complementarity of the combined use of culture-dependent and culture-independent methods regarding species detection and identification, which has been commonly employed since more than 20 years, but also the provision of both qualitative and quantitative data regarding species distribution.…”
Section: Sourdough Samplesupporting
confidence: 50%
“…Detecting and describing taxonomic novelty and reclassifying microbes has also been accomplished using MALDI-TOF MS ( Kudo et al, 2012 ; Wieme et al, 2012 ; Li L. et al, 2014 ; Praet et al, 2015 ; Yanokura et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acetic acid bacteria are Gram-stain-negative, obligately aerobic bacteria that produce acetic acid by ethanol oxidation and the genus Acetobacter is a representative acetic acid bacteria [1]. At the time of writing, the genus Acetobacter includes 28 validated published species that have been isolated from various alcoholic fermentation products such as in grapes, wine, water kefir, kombucha, beer, rice wine and cocoa bean and their vinegar products [2][3][4][5][6][7][8][9]. Cells of Acetobacter are motile or non-motile ellipsoidal to short rods usually showing catalase-positive and oxidase-negative activities and containing ubiquinone-9 (Q-9) as the predominant respiratory quinone.…”
mentioning
confidence: 99%